von Willebrand Factor Mediates Increased Platelet Retention in Recurrent Thrombotic Thrombocytopenic Purpura - Karpman, Diana; Lethagen, Stefan; Kristoffersson, AnnCharlotte; Isaksson, Christina; Holmberg, Lars (Thrombosis and Haemostasis, 1997)
The plasma cryoprecipitate of two brothers with recurrent thrombotic thrombocytopenic purpura (TTP) was previously found to mediate increased platelet retention and contain ultra-large von Willebrand factor (vWF) multimers during remissions. We conducted this study to examine if vWF is involved in the increased platelet retention in TTP. Platelet retention decreased when the patients’ plasma was incubated with a monoclonal antibody directed to the vWF epitope which interacts with the platelet receptor glycoprotein Ib or when incubated with a Fab-fragment directed to the platelet receptor glycoprotein IIb/IIIa. Replacement of patient vWF with an equivalent concentration of a factor VIII/vWF concentrate containing no ultra-large vWF multimers was accompanied by a normalization of platelet retention. These results indicate that vWF is involved in the increased platelet retention. Analysis of polymorphic markers in the vWF gene demonstrated that a recessive mutation in this gene is unlikely.